Influenza vaccination among Dutch general practitioners and their attitude toward influenza vaccination in the elderly - Ruud Andreas Fritz Verhees; Roy Snellings; Geert Jan Dinant; Johannes Andreas Knottnerus (Taylor & Francis Group, 2020)
Knowledge, attitudes and beliefs (KABs) toward influenza vaccination (IV) play a key role in HCWs' decisions to receive vaccination and can strongly influence patients' IV uptake. We examined the knowledge, attitudes and beliefs of GPs toward IV, exploring their opinion on IV in the elderly, mandatory HCW vaccination and the desirability of an IV trial in the elderly with hospitalization/mortality as effect measure. From November 2018 to March 2019, surveys were emailed to GPs and GP-practices (n = 1676) in three regions of the Netherlands. We assessed the self-reported IV in GPs, reasons for (not) advising IV to personnel, (not) supporting mandatory IV for personnel and (not) desiring a trial on IV in the elderly on hospitalization/mortality. Multivariable logistic regression models were used to determine predictors for GP IV. A total of 552 surveys were completed and 71.9% of the GPs reported receiving IV. Determinants for IV in GPs were male sex (aOR 1.62, 95%CI 1.06-2.49, p = .03) and age ≥60 y (aOR 5.25, 95%CI 1.51-18.32, p = .01). Seventy-nine percent of the GPs recommend IV for their practice personnel. Mandatory IV for personnel was supported by 41.2% of the GPs with GP self-reporting IV being the only determinant (aOR 10.03 (95%CI 5.69-17.70 p = .00)). An IV trial on hospitalization and/or mortality was desired by 60.5% of the GPs. We concluded that the majority of Dutch GPs receives IV and recommends IV to their personnel. These high rates along with the hesitancy of GPs toward mandatory HCW IV should be considered when policymakers decide on a mandate for IV in HCW in general.